Dental health care providers’ concerns, perceived impact, and preparedness during the COVID-19 pandemic in Saudi Arabia - Muhammad Qasim Javed; Farooq Ahmad Chaudhary; Syed Fareed Mohsin; Mustafa Hussein AlAttas; Hadeel Yaseen Edrees; Syed Rashid Habib; Arham Riaz (PeerJ, 2021)
Background Dental health care providers (DHCPs)are at high risk of cross-infection during clinical practice therefore, the aim of the study was to evaluate the DHCPs Covid-19 related concerns, its perceived impact, and their preparedness in Saudi Arabia. Methods This cross-sectional study on DHCPs was carried out at five dental teaching hospitals/colleges in four provinces of Saudi Arabia from October to December 2020. A 35-item valid and reliable questionnaire was used to assess the concerns, perceived impact, and preparedness of DHCPs in the COVID-19 pandemic. Chi-square tests and logistic regression were used to compare parameters between the clinical and non-clinical staff. Results A total of 320 DHCPs participated in this study with proportion of clinical staff (57.5%) surpassing the non-clinical staff (42.5%). The clinical DHCPs felt greater odds of falling ill with COVID-19 than non-clinical workers (OR, 2.61) and willing to look for another job (OR, 3.50). The higher proportion in both groups was worried that people close to them would be at higher exposure risk (96.3%) however, slightly more clinical DHCPs were concerned for their children than a non-clinical worker (OR, 3.57). The clinical DHCPs have greater odds of worrying that people would avoid them and their family members because of their job (OR, 2.75). A higher proportion in both groups (75.0%, 63.2%) felt that they would feel stress at work. More non-clinical DHCPs (94.1%) had received training for infection control than clinical (94.1% vs 63.0%: OR 0.10). Similarly, more DHCPs in the nonclinical group received adequate personal protective equipment training (88.2%; OR, 0.48). Most participants practiced self-preparation such as buying masks and disinfection (94.4%, 96.9%). Conclusion The majority of DHCPs felt concerned about their risk of exposure and falling ill from infection and infecting friends/family. These concerns could potentially affect the working of DHCPs during this pandemic. Measures to improve protection for DHCPs, minimize psychological implications, and potential social stigmatization should be identified at the planning phase before any pandemic.